Multidetector Computed Tomography (CT) Analysis of 168 Cases in Diabetic Patients with Total Superficial Femoral Artery Occlusion: Is It Safe to Use an Anterolateral Thigh Flap without CT Angiography in Diabetic Patients? - Suh, Hyunsuk Peter; Kim, Youngchul; Suh, Youngchul; Hong, JoonPio (Journal of Reconstructive Microsurgery, 2018)
Background The superficial femoral artery (SFA) is the most common site of lower extremity atherosclerosis, and collateral vessels from the deep femoral artery (DFA) play an important compensatory role between the iliofemoral segment and the popliteal artery. We examined SFA occlusion and collateral vessel developments in patients with diabetes mellitus using computed tomography (CT) angiography. We also compared the collateral systems from the DFA and the descending branch of the lateral circumflex femoral artery (dbLCFA) in the case of SFA occlusion.Methods We retrospectively reviewed 1,316 sets of CT angiographic data collected from 673 patients with diabetes between 2008 and 2010. The degree of stenosis in each segment of the proximal and distal SFA and the number and size of collateral vessels originating from the DFA and dbLCFA were measured using established scoring systems. In cases where the SFA was occluded, the numbers of collateral vessels originating from the DFA and the dbLCFA vessel were compared.Results The mean occlusion rate of the SFA was 15.6%. We noted that collateral vessels from DFA and dbLCFA were the main circulatory route in cases of occlusions of the SFA. More collateral vessels developed from the DFA than from the dbLCFA. Overall, 0.6% of the patients had only collateral systems from the dbLCFA.Conclusion When planning to use anterolateral thigh free flaps in diabetic patients with suspected SFA total occlusion, thorough investigations of the peripheral vessels are essential.
Keywords: diabetes; femoral artery; anterolateral thigh free flap